A Review Article: Impact of Using Critical Path Method (CPM) For Ship Repair Process - Afsari, Sabila Fitri; Marassabessy, Amir; Sulistyawati, Wiwin; Suranto, Purwo Joko; Djumiati, Andri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
Every ship that sails must be repaired to maintain seaworthiness and the safety of its users. Ship repairs that are carried out will take a considerable amount of time, so planning and scheduling must be completed before the repair process begins. The scheduling process at the shipyard is generally still done manually, involving the creation of a list of repairs. It has the potential to cause delays and increase the costs incurred. The use of the Critical Path Method (CPM) is an option to improve the effectiveness and efficiency of the repair process in terms of time and labor, and of course, minimize costs. This study aims to determine the effect of using the critical path method in the ship repair process, utilizing a literature review of several scientific articles. Of the 15 articles used in this study, 14 reported that the use of the critical path method enhances the effectiveness and efficiency of the ship repair process.